On the alternative punishment to the death penalty in China - Huang, Gui (Springer, 2024)
"This book presents a study of alternative penalties to the death penalty in China, aiming to promote theoretical exploration of death penalty reform in China as well as long-term penal reform. Currently, China is endeavouring to control the use of the death penalty and is gradually moving towards its abolition. The factors influencing the choice of the punishment option to replace the death penalty are complex and varied and include the traditional punishment culture, penalty concepts, the political system, the punishment system, public opinion and human rights, etc. Given the differences between China and developed Western democratic states, when we examine these influencing factors, we cannot ignore the culture of the punishment and the special political and legislation system in China. In this light, this work examined and analysed the factors that influence the choice of punishment option to replace the death penalty in this special political system with its clearly Chinese characteristics. Criminal policy and public opinion are two significant and typical factors involving obvious political considerations in China. The former normally reflects and carries out the will of the Government as expressed to the national management; the latter responds to the majority of citizens view on the current legal system and it is, to a great extent, the basis for national leaderships running of the country. Even though life imprisonment without release (hereinafter, LWOR) has been stipulated by the Ninth Amendment for the crime of corruption, it should not be the preferable option as the alternative sanction to the death penalty because it is a kind of cruel torture and violates the constitutional principle of human rights protection. On the contrary, life imprisonment with possibility of release (hereinafter, LWPR) would be an option, but the termination mechanisms for inmates should be set out in accordance with the principle of proportional justice; aggravated life imprisonment can be chosen to replace the death penalty in China. In addition, there needs to be improvements made to the relevant criminal systems. By examining China's death penalty reform and long-term imprisonment reform, this book not only explains the methodology of the reform theoretically, but also pays attention to the issues of legislation and judicial practice. This book is of interest to scholars and researchers in the fields of criminal justice, penal reform issues, and crime control in China." --